Development of probing strategies to investigate metabolic flux of biofuel production pathways in Clostridia - Wichlacz, Alexander Tomas (2018)
Currently, fossil fuels contribute a large number of high value chemicals that are used on a daily basis. Crude oil is cracked to give a number of high value chemicals, including vehicle fuels as well as chemicals and solvents that are used daily both commercially and industrially. However, fossil fuel reserves are in decline, with research going into alternatives to obtain these useful chemicals, one of which is biofuels.